Dual Repressive Function by Cip1, a Budding Yeast Analog of p21, in Cell-Cycle START Regulation - Li, Pan; Liu, Xueqin; Hao, Zhimin; Jia, Yanrong; Zhao, Xiangdong; Xie, Debao; Dong, Jingao; Zeng, Fanli (Frontiers in Microbiology, 2020)
Cip1, a newly identified yeast analog of p21, is a Cln3-CDK inhibitor that negatively regulates cell-cycle START. However, its function remains poorly understood. In this study, we found that deletion of CLN3 did not result in bypass of G1-phase arrest caused by Cip1 overexpression. Cip1 depletion in cln3-null mutants significantly advanced the timing of Cln2 expression, supporting the idea that Cip1 represses START in a Cln3-independent manner. We set to search for novel Cip1 interacting proteins and found that Ccr4, a known START regulator, and its associated factor Caf120, interact with Cip1. Ccr4-Caf120 acts redundantly with Cdk1-Cln3 to inhibit Whi5-mediated regulation of START. This interaction was conserved between human Ccr4 and p21. In addition, deletion of WHI5 robustly suppressed G1-phase arrest caused by Cip1 overexpression. We conclude that Cip1 negatively regulates START by acting as a dual repressor of Ccr4 in parallel with Cln3.